Habilidades sociales y conductas negativista desafiante de un adolescente con hipoacusia - Cobos Mendoza, Lenin Stalin; Naranjo Encalada, Victor Andres (Machala: Universidad Técnica de Machala, 2023)
Hearing impairment is a complex sensory and neurophysiological condition characterized by a reduced ability to perceive auditory stimuli. This condition can be congenital or acquired and it impacts the integrity of the auditory system, consequently affecting one's quality of life and social interaction. Therefore, the following study addresses the following scientific question, What factors influence the social skills and challenging oppositional behavior of a teenager with hearing impairment To answer this question, the overall objective of the research is to determine the factors that affect the social skills and challenging oppositional behavior of a teenager with hearing impairment. Regarding the methodology employed, we emphasized a qualitative approach and a descriptive research type. To ensure the credibility of our information, the following instruments were used: an observation guide, interviews, and the use of the Social Skills Scale EHS.The results obtained from the research provided insights into the factors that affect teenagers with hearing impairment in relation to the study variables, social skills and challenging oppositional behavior. The following factors were determined, lack of communication, poor upbringing, among others. Additionally, the Social Skills Scale SSS yielded a global percentile of 4, placing the teenager at a low level of social skills. In conclusion, the findings highlight that the student with hearing impairment lacks social skills and exhibits hostile behavior towards their family and environment.
La hipoacusia es una afección sensorial y neurofisiológica compleja que se caracteriza por la disminución para percibir estímulos auditivos. Esta enfermedad puede ser congénita o adquirida y afecta la integridad del sistema auditivo y con ello la calidad de vida y la interacción social. Por ende, el siguiente estudio plantea el siguiente problema científico, Qué factores afectan a las habilidades sociales y la conducta negativista desafiante de un adolescente con hipoacusia, para responder aquella interrogante, el objetivo general de la investigación es, Establecer los factores que afectan las habilidades sociales y conductas negativista desafiante de una adolescente con hipoacusia. Referente a la metodología empleada, se enfatizó desde un enfoque cualitativo y tipo de investigación descriptiva, así mismo para proporcionar veracidad a nuestra información se empleó los siguientes instrumentos, guía de observación, entrevista y el uso del test de Escala de Habilidades Sociales EHS. Los resultados obtenidos de la investigación, permitieron saber cuáles son los factores que afectan al adolescente con hipoacusia en relación con las variables del estudio, Habilidades sociales y conducta negativista desafiante, determinando así los siguientes factores como, falta de comunicación, mala crianza, etc. Así mismo en la Escala de Habilidades Sociales EHS se obtuvo un centil global de 4, ubicando al adolescente en un nivel bajo de habilidades sociales. Finalmente, las conclusiones se centran en que el estudiante con hipoacusia, carece de habilidades sociales y posee una conducta hostil con su familia y entorno.
Keywords: HIPOACUSIA; HABILIDAD; CONDUCTA; NEGATIVISTA